OP0038 Dose tapering and discontinuation of biological therapy in rheumatoid arthritis patients in remission in routine care – 2-year outcomes and identification of predictors. (12th June 2018) - Brahe, C.H.; Krabbe, S.; Østergaard, M.; Ørnbjerg, L.; Glinatsi, D.; Røgind, H.; Jensen, H.S.; Hansen, A.; Nørregaard, J.; Jacobsen, S.; Terslev, L.; Huynh, T.K.; et al.
Abstract : Background: A cohort of routine care rheumatoid arthritis (RA) patients in sustained remission had biological disease-modifying anti-rheumatic drugs (bDMARDs) tapered according to a treatment guideline. Little is known about predictors of successful tapering and discontinuation of bDMARDs. Objectives: We studied: 1) the proportion of patients whose bDMARD could be successfully tapered or discontinued; 2) unwanted consequences of tapering/discontinuation; 3) potential baseline predictors of successful tapering and discontinuation. Methods: One-hundred-and-forty-three patients with sustained disease activity score (DAS28-CRP)≤2.6 and no radiographic progression the previous year were included. bDMARD was reduced to 2/3 of standard dose at baseline, ½ after 16 weeks, and discontinued after 32 weeks. Patients who flared (defined as either DAS28-CRP≥2.6 and DAS28-CRP≥1.2 from baseline, or erosive progression on X-ray and/or MRI) stopped tapering and were escalated to the previous dose level. Results: One-hundred-and-forty-one patients completed 2 year follow-up. At 2 years, 87 patients (62%) had successfully tapered bDMARDs, with 26 (18%) receiving 2/3 of standard dose, 39 (28%) ½ dose and 22 (16%) having discontinued; 54 patients (38%) were receiving full dose. DAS28-CRP0–2yrs was 0.1((−0.2)–0.4) (median(interquartile range)) and mean Total-Sharp-Score0–2yrs was 0.01 (1.15) (mean(SD)). Radiographic progression was observed in 9 patients (7%). Successful tapering was independently predicted by: ≤1 previous bDMARD, male gender, low baseline MRI combined inflammation score and low MRI combined damage score. Negative IgM-rheumatoid factor predicted successful discontinuation. The association between potential predictors and the proportion of patients with successful tapering of bDMARDs is shown in figure 1. Conclusions: By implementing a clinical guideline, 62% of RA patients in sustained remission in routine care were successfully tapered, including 16% successfully discontinued at 2 years. Radiographic progression was rare. IgM-RF was an independent predictor for successful discontinuation of bDMARDs. Maximum one bDMARDs, male gender, and low baseline MRI combined inflammation and MRI combined damage scores were independent predictors for successful tapering. Disclosure of Interest: None declared